Identifying The Nssnps (Non-Synonymous Snps) Of Gene (SLC11A1) Involved In Spinal Tuberculosis - Sharma, Shubhra; Mishra, Amaresh; Singh, Rajan Kumar; Prakash, Amresh (Journal of Neonatal Surgery, 2025)
Single Nucleotide Polymorphisms (SNPs) play a vital role in understanding the genetic basis for several complicated human diseases. Additionally, knowing the functions of these SNPs might help us understand the genetics of human trait diversity. Identifying functional SNPs in a disease-related gene remains a major challenge. In this study, we have applied computational approaches to examine the genetic variation that can affect the SLC11A1 gene's expression and functionality. There were 7243 SNPs in all, 536 of them were missense/non-synonymous SNPs. Methods: We have employed a comprehensive analysis of the effect of all nsSNPs in the SLC11A1 gene using numerous methods like PolyPhen-2, PROVEAN, SIFT, I-Mutant, PANTHER, PhD-SNP, and Meta-SNP. The PolyPhen-2 identified 235 nsSNPs as probably damaging. PROVEAN shows 171 as deleterious nsSNPs. SIFT defines 163 nsSNPs as deleterious. I-Mutant has predicted 182 nsSNPs having decreased/increased stability. PANTHER found 262 nsSNPs as probably damaging, whereas PhD-SNP and Meta-SNP showed 214 and 243 as disease-associated mutations. Results: Comparing the predicted results from all these 7 methods, 11 nsSNPs rs139480250(Ala173Thr), rs141932707(IIe40Thr), rs145536242(Leu174Pro), rs150192588(Phe188Leu), rs151164925(Ser46Leu), rs182057473(Tyr395Cys), rs182057473(Tyr364Cys), rs201910426(Arg16Cys), rs367630718(Tyr94Cys), rs375775521(Gly271Ser), rs377166486(Asn362Ser) were found to be harmful. The study suggests the deleterious efficiency of these 11 nsSNPs in the SLC11A1 gene, which needs to be explored in relation to Spinal Tuberculosis. However, homology modeling and structural analysis were performed on previously empirically verified nsSNPs to ensure the predictability of projected models. The mutant models had higher energy and Root mean square deviation (RMSD) scores. Furthermore, FT-Site predicted one nsSNP, rs150192588(Phe188Leu) at the first binding region of the NRAMP1 protein out of the 11 picked-up nsSNPs. STRING predicted the functional interaction of the NRAMP1 protein. Conclusions: As a result of the current computational analysis, anticipated nsSNP may be a better pharmacological target contributing to treating and understanding spinal tuberculosis.